2014
DOI: 10.1787/9789264214262-en
|View full text |Cite
|
Sign up to set email alerts
|

How Was Life?

Abstract: This work is published on the responsibility of the Secretary-General of the oecD. The opinions expressed and arguments employed herein do not necessarily reflect the official views of the organisation or of the governments of its member countries This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. The statistical data for israel are suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 174 publications
0
17
0
2
Order By: Relevance
“…Piśmienność wpływa na poziom życia również w sposób pośredni, a to przez pozytywną korelację z produktywnością i wydajnością pracy, zdrowiem i higieną czy stabilnością polityczną, a także negatywną -ze zjawiskami takimi jak przemoc, przestępczość i nierówności społeczne 17 .…”
Section: Problem Badawczyunclassified
“…Piśmienność wpływa na poziom życia również w sposób pośredni, a to przez pozytywną korelację z produktywnością i wydajnością pracy, zdrowiem i higieną czy stabilnością polityczną, a także negatywną -ze zjawiskami takimi jak przemoc, przestępczość i nierówności społeczne 17 .…”
Section: Problem Badawczyunclassified
“…Several of these dimensions can be conceptualized through a capability lens and others (such as per capita GDP or real wages) are needed for a comparison between capability dimensions and income dimensions, or can be seen as core capability determinants or capability inputs. In a recent report, which reconstructed the outcomes on those dimensions between 1820 and 2000, it was found that some dimensions, such as education and health outcomes, are strongly correlated with per capita GDP, but others are not -such as the quality of political institutions, homicide rates and exposure to conflicts (Van Zanden et al 2014). Another example that illustrates the difference the capability approach can make is the analysis of gender inequality, for which it is clear that we are missing out the most important dimensions if we only focus on how income is distributed.…”
Section: A Yardstick For the Evaluation Of Prosperity And Progressmentioning
confidence: 99%
“…For example, one may simply want to describe how a country has developed over time in terms of a number of important functionings, as a way of giving information about the evolution of the quality of life that may give different insights than the evolution of GDP (e.g. Van Zanden et al 2014). Weighing dimensions is therefore not required for each capability theory or capability application, in contrast to the selection of dimensions, which is inevitable.…”
Section: C2: Weighing Dimensionsmentioning
confidence: 99%
“…For most of human history, what we now call "deprived" conditions were the norm. Two hundred years ago, 89% of humanity lived in extreme poverty (Ravallion 2016), 88% were illiterate (van Zanden et al 2014), and 43% of children died before they were five years old (Gapminder 2020).…”
Section: Introductionmentioning
confidence: 99%